Evaluation of Myocardial Perfusion by Computed Tomography - Principles, Technical Background and Recommendations - Magalhães,Tiago Augusto (2019)
Abstract Coronary computed tomography angiography (CCTA) has gained a prominent role in the evaluation of coronary artery disease. However, its anatomical nature does not allow the evaluation of the functional repercussion of coronary obstructions. It has been made possible to evaluate Myocardial computed tomography perfusion (Myocardial CTP) recently, based on myocardial contrast changes related to coronary stenoses. Several studies have validated this technique against the anatomical reference method (cardiac catheterization) and other functional methods, including myocardial perfusion scintigraphy and fractional flow reserve. The Myocardial CTP is performed in conjunction with the CCTA, a combined analysis of anatomy and function. The stress phase (with assessment of myocardial perfusion) can be performed before or after the resting phase (assessment of resting perfusion and coronary arteries), and different acquisition parameters are proposed according to the protocol and type of equipment used. Stressors used are based on coronary vasodilation (e.g. dipyridamole, adenosine). Image interpretation, similar to other perfusion assessment methods, is based on the identification and quantification of myocardial perfusion defects. The integration of both perfusion and anatomical findings is fundamental for the examination interpretation algorithm, allowing to define if the stenoses identified are hemodynamically significant and may be related to myocardial ischemia.